Visual Performances of a New Extended Depth-of-Focus Intraocular Lens with a Refractive Design: A Prospective Study After Bilateral Implantation - Spadea L; Giannico MI; Formisano M; Alisi L (Dove Medical Press, 2021)
Leopoldo Spadea, Maria Ilaria Giannico, Martina Formisano, Ludovico Alisi Eye Clinic, Policlinico Umberto 1, "Sapienza" University of Rome, Rome, ItalyCorrespondence: Leopoldo SpadeaHead Eye Clinic, Policlinico Umberto 1, "Sapienza" University of Rome, Via Benozzo Gozzoli 34, Rome, 00142, ItalyTel +39 06 519 3220Fax +39 06 8865 7818Email leopoldo.spadea@uniroma1.itPurpose: The aim of the present study was to evaluate the visual outcome of a new extended depth-of-focus (EDOF) intraocular lens (IOL) after bilateral implantation. A qualitative and quantitative analysis was performed and data were compared with those given by other studies regarding multifocal IOLs, which have the same purpose of giving spectacle independence to the patients.Methods: The study enrolled 40 eyes of 20 patients who underwent cataract surgery with bilateral implantation of an EDOF IOL (Evolve Soleko, Rome, Italy). The mean age was 74.5± 9 years (range 59- 83ys). Refractive outcomes and contrast sensitivity were evaluated preoperatively and at 6-month follow-up. We also examined reading speed, glare, halos, difficulties in the night driving, the requirement for spectacles, and overall satisfaction with vision. Two questionnaires were administered for this purpose.Results: At 6 months, the percentage of eyes within ± 0.50 diopters (D) from emmetropia was 82.5%. Of all patients, 90% were satisfied with their vision. The percentage of spectacle-free for near and distance vision patients was 70% and 95%, respectively. A postoperative binocular uncorrected 60cm intermediate visual acuity (UI60VA) of 0.2 logMAR or better was achieved in 92% of patients. Contrast sensitivity significantly improved postoperatively (p< 0.001) and mean reading speed was good.Conclusion: This new EDOF IOL seems to provide an effective alternative to patients who desire a spectacle-free lifestyle postoperatively. These lenses can supply a satisfactory distance, intermediate and near vision, and retain good contrast sensitivity, with most patients reporting excellent satisfaction.Keywords: cataract surgery, EDOF, IOL, presbyopia